HYBRID WARFARE – A TERM OF THE 21st CENTURY - Khatiashvili, Tamar (Online Journal of Humanities ETAGTSU, 2024)
In the past two decades, the term hybrid warfare has become one of the defining concepts in world politics. It refers to phenomena related to military, academic, and political aspects and their coverage in various types of media. However, due to the absence of standardized and unified military terminology in Georgian, the circulation of different forms of the term has become more prevalent. Along with "Hybrid War", other terms, such as "Hybrid Operations", Hybrid wars" and Hybrid war actions" have also been used. English terms such as hybrid war and hybrid warfare are often confused in Georgian texts or online articles, specifically in Georgian military manuals/doctrines by the Doctrine Development Center and online published scholarly manuals. Therefore, we focus on the following: • Expression of both English terms with one Georgian term. • Establishing several hybrid warfare matches, such as hybrid operations, hybrid wars, and hybrid combat operations. This paper aims to interpret the term hybrid warfare semantically and explore it based on English and Russian military doctrines. Understanding the essence of the source term is crucial in establishing its Georgian equivalent. The investigation into the history and etymology of this term is based on identifying the pattern, types and methods of hybrid warfare and treating current political phenomena as war or conflict. Based on the explored data, it becomes clear that its semantic interpretation is necessary for establishing a term. Changes in context can lead to the polysemy of the term and its incorrect usage. The problem of harmonization of present-day terminology work comes to the foreground in search of adequate Georgian equivalents of the English terms. It is crucial to involve military specialists in establishing an appropriate term due to their great interest in the matter. Full Text (PDF)